The Effect of Service Quality, Trust and Customer Satisfaction on the Behavioural Intention of BTN Batara Savings Customers at Bank BTN KC Depok - Nurul Hasanah; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of service quality, trust and customer satisfaction on the behavioural intention of BTN Batara Savings customers at Bank BTN KC Depok. The sample in this study was 100 respondents who used BTN Batara Savings at Bank BTN KC Depok. This study used primary data with a data collection method through questionnaires distributed to 100 respondents. Data analysis techniques using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) program version 24.0. From the results of multiple linear regesion analysis, using a t test where Service Quality (X1) does not have a positive and significant effect on Behavioural Intention because it has a total score of -2.083 < 1.984. Trust (X2) has a positive and significant effect on Behavioural Intention with a score of 2,193 > 1,984 and Customer Satisfaction (X3) has a positive and significant effect on Behavioural Intention with a score of 3,599 >1,984. So it can be concluded that Service Quality does not have a positive effect on Behavioural Intention, while Trust and Customer Satisfaction have a positive and significant influence on Behavioural Intention.